A Theoretical Investigation of the Decomposition and Reactivity of the CHF2CF2CF2OCH2O Radical from HFE-356pcc3 between 200 and 400 K. (May 2017) - Hoseinpour, Sajedin; Izadi-Vasafi, Hossein; Azimi, Mona; Kazemi, Ali
This investigation involves the ab initio quantum mechanical study of the decomposition and reactivity of the CHF2 CF2 CF2 OCH2 O radical that is formed from CHF2 CF2 CF2 OCH3 (HFE-356pcc3). The geometries of the reactants, products and transition states were optimised at the B3LYP and B3PW91 levels of theory using the 6-311G(d, p) basis set. Five important pathways for the decomposition and reactivity of CHF2 CF2 CF2 OCH2 O were investigated: (1) reaction with atmospheric O2, (2) reaction with atmospheric OH radical, (3) C–O bond cleavage, (4) H elimination and (5) the migration of hydrogen from carbon to oxygen and then C–O bond cleavage, with energy barriers of 4.4 (5.0), 11.9 (12.4), 17.0 (17.3), 20.4 (19.4) and 32.2 (32.6) and 15.5 (16.7) kcal mol −1 respectively [values in parentheses are for the B3PW91/6-311G(d, p) level of theory]. Rate constants were calculated by utilising canonical transition state theory in the range 200–400 K and the corresponding Arrhenius diagrams have been plotted. The results showed that the rates of decomposition and reaction increase with increasing temperature. Also, between 200 and 306 K, path (1) has the highest rate constant: moreover, it was concluded that reaction with atmospheric O2 is the dominant pathway for the consumption of CHF2 CF2 CF2 OCH2 O in the atmosphere. An intrinsic reaction coordinate calculation was performed to confirm the existence of a transition state on the corresponding potential energy surface.